# Deriving Constraints in the dual form of SVM

In a regular soft-margin SVM we want to find

$$\min_{w,b, \xi} \frac{1}{2}||w||^2+C\sum_{i=1}^{\ell}\xi_i$$

subject to $$y_i((w,x_i),+b) \geq 1 - \xi_i$$

and $$\xi_i \geq 0$$

Which we convert to the Lagrangian

$$L(w, b, \alpha, \beta) = \frac{1}{2}||w||^2+C\sum_{i=1}^{\ell}\xi_i - \sum_{i=1}^{\ell}\alpha_i[y_i((w,x_i)+b)-1+\xi_i] - \sum_{i=1}^{\ell}\beta_i \xi_i$$

To find the minimum with respect to $$w,b,\xi$$ we find where the gradient is the 0 vector, giving

\begin{aligned} \frac{\partial L}{\partial w} & = w - \sum_{i=1}^{\ell}\alpha_i y_i x_i = 0 \\ & \equiv w - \sum_{i=1}^{\ell}\alpha_i y_i x_i = 0 \\ & \equiv w = \sum_{i=1}^{\ell}\alpha_i y_i x_i \\ \end{aligned}

\begin{aligned} \frac{\partial L}{\partial b} & = \sum_{i=1}^{\ell} -\alpha_i y_i = 0 \\ & \equiv \sum_{i=1}^{\ell} \alpha_i y_i = 0 \\ \end{aligned}

\begin{aligned} \frac{\partial L}{\partial \xi} & = \sum_{i=1}^{\ell}C-\sum_{i=1}^{\ell}\alpha_i-\sum_{i=1}^{\ell}\beta_i = 0\\ & \equiv \sum_{i=1}^{\ell}C = \sum_{i=1}^{\ell}\alpha_i+\beta_i \\ \end{aligned}

My question is this.... In every text I look at, (such as pg.8 of these teaching notes or implied in pg.20 of these course notes) the last equation ($$\frac{\partial L}{\partial \xi}$$) results in $$C=\alpha_i + \beta_i$$ without the summation. Can anybody explain to me how this leap is made?

Because ξ is a vector, and in the first link you will see they derive it per every element. more specifically: $$\frac{\partial C}{\partial \zeta_i} = C - \alpha_i - \beta_i$$
$L(w,b,\alpha,\beta) = ... C\sum_i^l\zeta_i - \sum_i^l\alpha_i\zeta_i - \sum_i^l\alpha_i\zeta_i$
$L(w,b,\alpha,\beta) = ... \sum_i^l({C\zeta_i -\alpha_i\zeta_i - \beta_i\zeta_i )} = ...\sum_i^l{\zeta_i(C - \alpha_i - \beta_i )}$
And from here we can see that the derivative with respect to $\zeta_i$ is 0 only if $C - \alpha_i - \beta_i=0$